2019
DOI: 10.1097/id.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of One-Abutment at One-Time on Marginal Bone Loss Around Implants Placed in Healed Bone

Abstract: The primary aim of the present article was to review the effect and the clinical significance of abutment dis-and reconnection on the peri-implant marginal bone levels.Materials and methods: English articles published from 2009 to April 2019 were identified on the MED-LINE, Cochrane Library, and PubMed databases, according to the PRISMA guidelines. Comparative in vivo studies on humans were included.Results: A total of 4 studies with different levels of bias were included in this review. A significant heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
0
15
0
5
Order By: Relevance
“…However, in this study the healing abutments were removed within a limited number of times (3 times) in order to limit the damage of soft tissues. In addition, recent studies have shown that clinically this can have an extremely limited effect and other factors may have a greater influence [42,43]. Moreover, during the healing period the test HAs used in this study have not been removed.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study the healing abutments were removed within a limited number of times (3 times) in order to limit the damage of soft tissues. In addition, recent studies have shown that clinically this can have an extremely limited effect and other factors may have a greater influence [42,43]. Moreover, during the healing period the test HAs used in this study have not been removed.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, MUAs allow placement of the definitive abutment at the time of implant placement which may further decrease marginal bone loss. 17 The creation of stable soft tissue around the transmucosal portion of the implant is critical to the long-term implant health. This biologic seal preserves crestal bone levels, supports peri-implant soft tissues, and provides a soft tissue seal against microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated removal and replacement of the abutment disrupts the soft tissue attachment and leads to additional marginal bone loss. 17,19,20 A multi-unit abutment best accomplishes these goals.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of this multicenter cohort study was to investigate the association of the one‐abutment one‐time concept with MBL around bone‐level implants in relation to other factors. The high number of systematic reviews that have been published on the topic may reflect the interest on maximal bone preservation by the scientific community (Atieh et al., 2017; Perrotti et al., 2019; Santos et al., 2018; Wang et al., 2017). Systematic reviews on therapeutic aspects are usually based on RCTs.…”
Section: Discussionmentioning
confidence: 99%